2017
DOI: 10.1038/ncomms14187
|View full text |Cite
|
Sign up to set email alerts
|

A cocktail of three virulent bacteriophages prevents Vibrio cholerae infection in animal models

Abstract: Effective prevention strategies will be essential in reducing disease burden due to bacterial infections. Here we harness the specificity and rapid-acting properties of bacteriophages as a potential prophylaxis therapy for cholera, a severely dehydrating disease caused by Vibrio cholerae. To this end, we test a cocktail of three virulent phages in two animal models of cholera pathogenesis (infant mouse and rabbit models). Oral administration of the phages up to 24 h before V. cholerae challenge reduces coloniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(153 citation statements)
references
References 23 publications
1
140
0
4
Order By: Relevance
“…But earlier studies showed the use of cocktail of phages to eliminate the bacterial infection [21, 22]. This study shows that the effectiveness of phage therapy depends only of the ability of single phage to reduce the bacterial load and not on the complexity of phage preparations.…”
Section: Discussionmentioning
confidence: 77%
“…But earlier studies showed the use of cocktail of phages to eliminate the bacterial infection [21, 22]. This study shows that the effectiveness of phage therapy depends only of the ability of single phage to reduce the bacterial load and not on the complexity of phage preparations.…”
Section: Discussionmentioning
confidence: 77%
“…The encapsulated dose was ~ 2 x 10 8 PFU g -1 of phage microparticles. One gram of microparticles would therefore deliver a ~10 7 PFU dose which is similar to therapeutic doses given in a number of animal studies [28], [8589]. Nale et al [28] in their hamster C .…”
Section: Discussionmentioning
confidence: 81%
“…; Yen et al . ). However, in order to further develop phages as antimicrobial agents, it is necessary to investigate the impact of more complex formulations which include additional active and excipient components (Abedon ).…”
Section: Resultsmentioning
confidence: 97%